Pengaruh Perbedaan Ketinggian Tumbuh Daun Miana (Coleus scutellarioides) di Daerah Bali Terhadap Kadar Flavonoid Total - Puspita Sari, Dyah Ratna Ayu; Ugrasena, Putu Yudha; Indraswari, Putu Ika Indah (Herbal Medicine Journal, 2025)
Miana (Coleus scutellarioides) contains flavonoids as its primary active components and is widely used in traditional medicine, particularly in Indonesia. In Bali, which is renowned for its traditional healing practices (Usada Bali), miana is commonly utilized as a herbal remedy. The leaves of miana possess various pharmacological activities, including anti-inflammatory, antiproliferative, antidiabetic, anthelmintic, and antipyretic effects. Geographical conditions, such as the altitude of the growing region, are among the factors that influence the flavonoid content in miana leaves. This study aimed to determine the total flavonoid content in miana leaves from three different altitudes in Bali: Bedugul (1273 masl), Klungkung (393 masl), and Sanur (11 masl). An experimental laboratory design was employed, using maceration with 96% ethanol as the extraction method. The total flavonoid content was quantified using UV-Vis spectrophotometry, with quercetin as the reference standard. The results showed that miana leaves from Klungkung exhibited the highest total flavonoid content (540.85 ± 7.97 mgQE/g), followed by Bedugul (488.68 ± 6.07 mgQE/g) and Sanur (368.53 ± 11.2 mgQE/g). Statistical analysis revealed that the total flavonoid content of miana leaves from Klungkung was significantly higher (P<0.05) than that from the other two regions. These findings indicate that the altitude of the growing region affects the total flavonoid content in miana leaves, with the highest levels observed at an intermediate altitude (393 masl).